Ashamed of One’s Sexism, Mourning One’s Friends: Emotions and Relations in Men’s Encounters with Feminism in Sweden - Berggren, Kalle (Culture Unbound, 2021)
One of the most important questions for feminist research on men and masculinity concerns how men can change and become more affected by feminism and less engaged in sexism. Here, men who identify as feminist, pro-feminist or anti-sexist have been considered to be of particular interest. This article contributes to the emerging research on men’s engagement with feminism by analysing contemporary writing about gender relations, inequality and masculinity, more specifically books about men published in Sweden, 2004-2015. Focusing on lived-experience descriptions, the analysis shows how a range of emotions are central to the processes where men encounter and are becoming affected by feminism. The emotions identified include happy ones such as relief, but a more prominent place is given to negative emotions such as alienation, shame, frustration, as well as loss and mourning. Drawing on Ahmed’s model of emotions as bound up with encounters with others, the article highlights how men’s engagement with feminism is embedded within interpersonal relations with others, particularly women partners, men friends, and children.